PENGARUH PENDEKATAN CRT DALAM MENINGKATKAN HASIL DAN MOTIVASI BELAJAR SISWA - Mandasari, Junika; Titin, Titin; Juniardi, Dodi (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2024)
The research aims to improve students' learning outcomes and learning motivation through the application of a Culturally Responsive Learning (CRT) approach to the learning process. This study is a two-cycle class action study, where one cycle meets through planning stages, evaluation and reflection. The subject of this study was the XI Ipa 2 class with 32 students. Cycle 1 students' learning results obtained an average score of 79.93 to 75% and cycle 2 students' learning results obtained an average score ofÂ  87.70 to 87.50%. The student's best learning motivation is to challenge indicators or to solve problems by showing positive statements as well as interesting learning activities. Based on the data results obtained from the 1st and 2nd cycle learning process, this CRT approach can improve the learning results and motivation of XI Ipa 2 class students from State High School 05 Pontianak.